Pretreatment Plasma EBV-DNA Load Guides Induction Chemotherapy Followed by Concurrent Chemoradiotherapy in Locoregionally Advanced Nasopharyngeal Cancer: A Meta-Analysis - Lai, Lin; Chen, Xinyu; Zhang, Chuxiao; Chen, Xishan; Chen, Li; Tian, Ge; Zhu, Xiaodong (Frontiers in Oncology, 2021)
Background: The efficacy of induction chemotherapy (IC) followed by concurrent chemoradiotherapy (CCRT) in locoregionally advanced nasopharyngeal cancer (LA-NPC) is controversial. In this paper, we conducted a meta-analysis based on relevant studies to provide strong evidence for clinical strategies. Materials and Methods: We searched the MEDLINE, Embase, Cochrane, PubMed, and Web of Science databases for studies that stratified patients based on a high or low plasma Epstein-Barr virus deoxyribonucleic acid (EBV-DNA) load before treatment and compared the clinical efficacy of IC+CCRT versus CCRT alone in locoregionally advanced NPC. We tested for heterogeneity of studies and conducted sensitivity analysis. Subgroup analysis was performed for overall survival (OS), progression-free survival (PFS), distant metastasis-free survival (DMFS), and locoregional relapse-free survival (LRFS). Results: Seven studies with a total of 5289 cases were finally included in the meta-analysis. The heterogeneity test revealed the homogeneity of OS (I2=0.0%, p=0.794), PFS (I2=0.0%, p=0.778), DMFS (I2=0.0%, p=0.997), and LRFS (I2=0.0%, p=0.697) in patients with EBV-DNA loads of ≥4000 copies/ml in the both IC+CCRT and CCRT groups. The results unveiled that IC+CCRT significantly extended the OS (HR 0.70 [95% CI 0.58-0.83], p=0.000), PFS (HR 0.83 [95% CI 0.70-0.99], p=0.033), and DMFS (HR 0.79 [95% CI 0.69-0.9]，p=0.000) of patients compared with the CCRT group, but no beneficial effects on LRFS (HR 1.07 [95% CI 0.80-1.42], p=0.647). The heterogeneity test found that there was no significant heterogeneity of PFS (I2=0.0%, p=0.564), DMFS (I2=0.0%, p=0.648), LRFS (I2=22.3%, p=0.257) and OS (I2=44.6%, p=0.164) in patients with EBV-DNA loads of <4000 copies/ml. The results showed that IC+CCRT prolonged DMFS (HR 0.57 [95% CI 0.39-0.85], p=0.006) of patients, without significant improvements in OS (HR 0.88 [95% CI 0.55-1.26], p=0.240), PFS (HR 0.98 [95% CI 0.74-1.31], p=0.908), and LRFS (HR 0.98 [95% CI 0.54-1.77]，p=0.943). Conclusions: Pretreatment plasma EBV-DNA can be considered as a promising effective marker for the use of IC in LA-NPC patients. The addition of IC could improve the OS and PFS of patients with EBV-DNA load ≥4000 copies/ml, but no efficacy in patients with EBV-DNA load <4000 copies/ml. Moreover, regardless of the EBV-DNA load, IC could improve DMFS but no effect on LRFS.